Hubungan antara Status Sosial Ekonomi Keluarga dengan Motivasi Belajar Peserta Didik Program Kesetaraan Paket C di SKB Gresik - Runnanda, Wahyu Abbiyah Qoth; Mardliyah, Sjafiatul (J+PLUS UNESA, 2024)
This research was motivated by problems regarding learning motivation in students of the package C equivalence program at Gresik Learning Activity Studio during learning which was indicated to lack motivation to learn. There are factors that influence learning motivation is an extrinsic factor, namely family socioeconomic status. The purpose of this study was to analyze the socioeconomic status and learning motivation of students of package C equivalence program at Gresik Learning Activity Studio and show the relationship between family socioeconomic status and learning motivation of students of package C equivalence program at Gresik Learning Activity Studio. This study used quantitative methods with Spearman Rank correlation analysis techniques. The data collection technique used in this study was questionnaires and documentation with research respondents as many as 32 students of the Gresik Learning Activity Studio package C equivalence program. The results showed that family socioeconomic status has a positive and significant relationship with the learning motivation of Package C students at Gresik Learning Activity Studio which is indicated by a significance value of 0.013<0.05 and a correlation coefficient value of 0.432, this means that the higher the socioeconomic status of the families of students of the package C equivalence program at Gresik Learning Activity Studio, the higher the learning motivation, or vice versa, the lower the socioeconomic status of the students' families, the lower the learning motivation.